Mackerel Fish Cracker Productions Offort In The Karimun District Karimun Regencybriau Archipelago Province - Sepra, Melania; Yulinda, Eni; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in february 2014 ocated in Karimun district Karimun Regency Riau Archipelago Pronvince. Locatian determination is done on purpose as place of research with the basis that there are in Karimun District mackerel fish prossing business into Amplang mackerel crakers. Respondent in this research is the awner business processing mackerel crakker and i employe who works in this business. While consumers and 1 employe who wroks in this busniess. White consumens and marchants who become an informant to obtain supporting data on processed product mackerel crackers.The number of worker in the fish processing business mackerel crackerel as much as 3 people in a onetime processing/ production of fish crackerel processing business is capable of processing up to scopacks, sizes who offerest are heary 1½ ons weight, ptice rp 15.000,- ½ kg weight rp 55.000,- and the weight 1 kg isrp 110.000,-. With an average monthly income is rp 5.284.200,-. Mackerel marketing area is Karimun and Tg,pinang, including, supermarkets, arport and harbor swalayan. The presence the other fish crackers processed mart intocompetition price by mackerel fish crackers product to be very nigh, because processed fish crackers other than mackere lable to well below the price of mackerel creckers. But while the other of procesed crackers offer a low price, mackerel crackers is able to survive because of the this mackerel fish crackers has differenttaste more than other fish crackers.Keyword ; Crackers, Mackerel, Price